Voc transient in silicon heterojunction solar cells with µc-SiOx:H window layers. (2nd July 2018) - Yang, Xueliang; Song, Jianmin; Yang, Jing; Bai, Jingjing; Dang, Wei; Chen, Jianhui
Abstract: Silicon heterojunction (SHJ) solar cells with hydrogenated microcrystalline silicon oxide ( µ c-SiO x :H) emitters are fabricated and studied using the open circuit voltage ( V oc ) transient. The built-in electric field ( E in ), minority carrier lifetime, hole mobility, and a-Si:H/c-Si heterointerface valance band offset (Δ E v ) of the solar cells can be excavated by the V oc transient. The rising rate of the V oc transient curve, which has not been studied in previous research, is found to be dependent on E in in SHJ cells. The measurements of the V oc transient curves at different excitation intensities are used as a powerful approach for analysis of the Δ E v difference between SHJ cells with different µ c-SiO x :H emitters. Based on this analysis, it is demonstrated that the origin of the S-shaped J – V characteristics of SHJ cells lies in an inferior E in and/or severe interface Δ E v, and the role of Δ E v is more dominant.